Self-wavelength-sweeping in a bi-directional thulium-doped fiber ring laser. (27th March 2019) - Jiang, Hongbo; Zhao, Zihao; Jin, Lei; Set, Sze Yun; Yamashita, Shinji
Abstract: We report for the first time the self-wavelength-sweeping phenomenon of a bi-directional thulium-doped fiber ring laser. The laser wavelength can spontaneously sweep in both lasing directions at a rate up to 0.2 nm s −1 over 15 nm sweeping range in the 1.95 μ m wavelength region. The sweeping rate can be controlled by simply changing the state of polarization of the laser cavity. The laser can be tuned to generate a periodical wavelength-swept output with microsecond pulses in the time domain. The sweep rate can also be tuned to zero to give a static lasing wavelength.